Visible Light as the Key for the Formation of Carbon–Sulfur Bonds in Sulfones, Thioethers, and Sulfonamides: An Update - Azzi, Emanuele; Lanfranco, Alberto; Moro, Riccardo; Deagostino, Annamaria; Renzi, Polyssena (Synthesis, 2021)
This review summarizes the most relevant advancements made in the photocatalyzed synthesis of sulfones, thioethers, and sulfonamides from 2017 to the beginning of 2021. Synthetic strategies towards the construction of sulfur–carbon bonds are discussed together with the proposed reaction mechanisms. Interestingly, sulfur-based functional groups, which are of fundamental importance for the pharmaceutical field, can be assembled by photocatalysis in an easy and straightforward way under milder reaction conditions employing less toxic and expensive sulfur sources in comparison with common strategies.1 Introduction2 Sulfones2.1 Sodium Sulfinates and Sulfinic Acids2.2 Sulfonyl Halides2.3 Sulfonyl Hydrazones2.4 Sulfur Dioxide Surrogates2.5 Miscellaneous3 Thioethers4 Sulfonamides5 Conclusions
Keywords: photocatalysis; sulfones; thioethers; sulfonamides; sulfur radicals